Internalisasi nilai moderasi beragama melalui Pendidikan Agama Islam di lembaga pendidikan dasar desa Pancasila Balun Turi Lamongan - Lusia Mumtahana; Ahmad Hanif Fahruddin; Wahyuni Ahadiah; Ayu Afita Sari (Institut Agama Islam Al-Hikmah Tuban, 2022)
The purpose of this study is to describe the strategies used by educators at State Elementary Schools 1, State Elementary Schools 2, and MI Tarbiyatus Sibyan Balun Turi Lamongan as elementary schools in multi-religious villages to instill the values of religious moderation, as well as the implementation of moderation values. which is applied by the main educators in religious education at State Elementary Schools 1, State Elementary Schools 2, and MI Tarbiyatussibyan Balun Turi Lamongan to students. State elementary schools 1 and 2 Balun Turi Lamongan is a multi-religious elementary school that has a variety of cultures, races, ethnicities, and religions, therefore it is not uncommon for these differences to lead to conflict, including at MI Tarbiyatussibyan where their living environment intersects with a multi-religious community. From an early age, extreme and radical thoughts must be eliminated as soon as possible. This study uses a descriptive qualitative method with a phenomenological approach. From the results of the research that we got at State Elementary Schools 1, State Elementary Schools 2, and MI Tarbiyatussibyan Balun Turi Lamongan, a strategy for inculcating the value of religious moderation is applied in teaching and learning activities and outside teaching and learning activities. There are many ways that educators do in inserting knowledge about attitudes and values of diverse moderation as well as mutual respect and tolerance in every learning and habituation. State Elementary Schools 2 and MI Tarbiyatussibyan Balun Turi Lamongan is a strategy for inculcating the value of religious moderation applied in teaching and learning activities and outside teaching and learning activities. There are many ways that educators do in inserting knowledge about attitudes and values of diverse moderation as well as mutual respect and tolerance in every learning and habituation. State Elementary Schools 2 and MI Tarbiyatussibyan Balun Turi Lamongan is astrategies for inculcating the value of religious moderation applied in teaching and learning activities and outside teaching and learning activities. There are many ways that educators do in inserting knowledge about attitudes and values of diverse moderation as well as mutual respect and tolerance in every learning and habituation.